As dunas eólicas de Natal/RN: datação e evolução - Silva, Elisangela Alves de Jesus (2002)
The main purpose of this study is to present complementary information on eolian systems that occur in the Center-South portion of the city of Natal, Rio Grande do Norte State, Brazil. The investigation focused on the identification of eolian units, absolute luminescence dating of eolian sediments, to geophysical analysis by Ground Penetrating Radar (GPR), as well as qualitative identification of the use and terrain occupation in the study area. A map was elaborated in order to separate eolian geological units, and describe their deposicional and erosional characteristics, by aerial photo-interpretation. The study lead to the identification of six main units: Unit I - Blowouts (BW), Unit II - Active dunes field (DA), Unit III - Fixed dunes field (DF), Unit IV - Parabolic dunes field (DP), Unit V - Red parabolic dunes field (DV) and Unit VI - Devastated dunes surface (SD). Were analised by Termoluminescense (TL) Method Eight samples from units I, III, IV and V. The largest number of samples with similar or close resulted yielded ages about 15,000 years. Two GPR profiles were obtained in areas of the Dunes Park, near the "Natal s Conventions Center". Results showed the migration a new dune generation over on older one, the geologic contact between dunes and the Formação Barreiras (FB), and the groundwater level inside the dune unit. The qualitative study on the use and terrain occupation of the soil in some dunes fields in the study area, it was possible identify some use and occupation, as the following ones: the construction of residential and commercial buildings, dunes fields cutted for construction to access road and garbage deposition